Conventional management of Spodoptera exigua in crops of the municipality of Los Reyes de Juárez, Puebla - Barrientos-Gutiérrez, Javiera Estefany; Huerta-de la Peña, Arturo; Escobedo-Garrido, José Sergio; López- Olguín, Jesús Francisco (Revista Mexicana de Ciencias Agrícolas, 2018)
Spodoptera exigua is an agriculturally important insect pest worldwide that affects a variety of crops, among which are ornamental, grains and vegetables. The control methods used are synthetic chemical insecticides; however, there have been reports regarding changes in susceptibility to various insecticides. This adaptation has been increasing, and there are reports of a large number of insecticides to which S. exigua has developed resistance. In the municipality of Los Reyes de Juárez, Puebla management information was obtained of this insect and crops affected by simple random sampling with maximum variance, obtaining a sample size n= 160 producing a total of 1 300 registered 2007 agricultural census. The application of semi-structured survey was conducted in August, 2011 to January, 2012. The results indicated that, the most affected crops by S. exigua were: spinach, broccoli and cabbage. The conventional insecticides used in the control of this insect were: Chlorpyrifos-ethyl+ Permethrin (22.7%) and Carbofuran (21.8%). The advice on the use of insecticides for the control of S. exigua is provided by the vendors of commercial houses of agrochemicals (33.1%) or did not receive any help at all (49%). More than half of the farmers (59%) commented to conduct themselves applying insecticides, without any advice. Finally 18.7% of farmers reported having experienced some intoxication as a result of their exposure to the insecticides used in the management of armyworm.
Keywords: S. exigua; vegetables; insecticides; armyworm; pests